2012
DOI: 10.1021/jo301793z
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Bond-Driven Electrophilic Activation for Selectivity Control: Scope and Limitations of Fluorous Alcohol-Promoted Selective Formation of 1,2-Disubstituted Benzimidazoles and Mechanistic Insight for Rationale of Selectivity

Abstract: Hydrogen-bond-driven electrophilic activation for selectivity control during competitive formation of 1,2-disubstituted and 2-substituted benzimidazoles from o-phenylenediamine and aldehydes is reported. The fluorous alcohols trifluoroethanol and hexafluoro-2-propanol efficiently promote the cyclocondensation of o-phenylenediamine with aldehydes to afford selectively the 1,2-disubstituted benzimidazoles at rt in short times. A mechanistic insight is invoked by NMR, mass spectrometry, and chemical studies to ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(52 citation statements)
references
References 63 publications
1
48
0
1
Order By: Relevance
“…The nature of the chemical reactions can be controlled by the influence of weak interactions or soft force . Therefore, many reactions are designed by exploring cooperative multiple non‐covalent interactions like hydrogen bonding, halogen bonding, hydrophobic effect, cation‐π, anion‐π, etc . Our research goal is encircled in understanding the reactivity of non‐prefunctionalized substrates by weak or noncovalent interactions .…”
Section: Resultsmentioning
confidence: 99%
“…The nature of the chemical reactions can be controlled by the influence of weak interactions or soft force . Therefore, many reactions are designed by exploring cooperative multiple non‐covalent interactions like hydrogen bonding, halogen bonding, hydrophobic effect, cation‐π, anion‐π, etc . Our research goal is encircled in understanding the reactivity of non‐prefunctionalized substrates by weak or noncovalent interactions .…”
Section: Resultsmentioning
confidence: 99%
“…The satisfactory results from these scale-up experiments further confirmed the advantage of this simple and "green" protocol for its potential in large-scale synthesis. a) General conditions: o-phenylenediamine (1 mmol) and Ia (2 mmol) in lactic acid (2 mL), stirred at ambient temperature for 4-6 h; b) yield of isolated product; c) values reported in literature Chebolu et al, 2012;Ahmadian et al, 2015); d) reaction at 80 • C and purified by silica gel column chromatography. From the experimental observations and literature reports on experiments carried out under similar reaction conditions , a plausible reaction mechanism for the selective formation of 1,2-substituted benzimidazoles in lactic acid was proposed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several methods have been reported for the selective synthesis of 1,2-disubstituted benzimidazoles using FeF 3 , Me 3 SiCl (Wan et al, 2009), ZnO-NPs (Sharma et al, 2015), HClO 4 -SiO 2 as catalyst or microwave irradiation in acetic acid (Azarifar, 2010), ultrasonic irradiation (Kumar et al, 2014). In addition, Chebolu et al (2012) reported a metal/Lewis acid-free protocol in which fluorous alcohols with better hydrogen bond donor (HBD) abilities could efficiently promote the selective formation of 1,2-disubstituted benzimidazoles.…”
Section: Introductionmentioning
confidence: 99%
“…[28,32] Moreover, trace amount (6 %) of imine B (2-(benzylideneamino)aniline) was found during this process in this experiment, which was somewhat different from the process with Cu or Ru as the catalysts. [29,33] Scheme 2. The oxidative coupling of benzyl cyanides with tert-butyl hydroperoxide.…”
Section: The Capture Of Intermediatesmentioning
confidence: 99%